Síntese física e caracterização de pontos quânticos de tungstênio - Santos, Raquel de Oliveira dos (2022)
Quantum Dots (Qds) are semiconductor nanoparticles with size that is smaller than their exciton Bohr radius. Due to the small dimensions, quantum confinement occurs in these nanomaterials, differentiating them from the bulkshaped material. In particular, the electrical and optical properties of QD sare size dependent and therefore can be controlled. This customization possibility makes Qds interesting for applications in several areas, particularly for the development of sensors and biosensors. In this work, we present results on the synthesis and characterization of tungsten quantum dots obtained from laser ablation in liquid medium (LASiS– Laser Ablation Synthesis in Solution). Our experimental results include the production of Qds using two different solvents: acetone and bidistilled water. The syntheses were performed under an experimental setup based on the fundamental harmonic and the first harmonic (532 nm) of a Nd:YAG laser operating in QS mode. After the synthesis process, the colloids were characterized by Dynamic Light Scattering (DLS) and Transmission Electron Microscopy (TEM) techniques to determine nanoparticle size. The synthesis parameters were adjusted to obtain spherical nanoparticles with diameters below 10 nm, which is compatible with Qds for tungsten. In addition, the UV-Vis technique was used to characterize the optical absorption and identify the bandgaps which lie in the ultraviolet region. The samples produced were also subjected to photoluminescence measurements, resulting in emission bands centered at 440 nm and 488 nm, in the blue region of the electromagnetic spectrum and visible to the naked eye. The tungsten quantum dot production proccess used in this work proved to be highly effective for the production of photoluminescent nanoparticles with low size dispersion and could be an interesting alternative for the green synthesis of colloidal suspensions containing Qds from a material that presents biocompatibility. The synthesized tungsten Qds are intended to be used in techniques aiming for the detection and characterization of biological materials, particularly cellular biomarkers.